Interaction and the standardized survey interview : - Houtkoop-Steenstra, Hanneke (Cambridge University Press, 2000)
This is the first study of investigate in detail the interaction between interviewers and respondents in standardized social survey interviews. he Hanneke Houtkoop-Steenstrarules offers the normal conversation fail to apply in form-based interviews, original empirical evidence to show what really happens, tools of conversation analysis and points to ways of improving survey compilation and the validity of data.